The Implementation of the DaM2R Strategy to Increase the Acceleration of Student Thesis Writing - Joko Susilo, Mohamad (The Indonesian Institute of Science and Technology Research, 2025)
This research aims to increase the acceleration of students' cognitive abilities in writing a thesis through the DaM2R strategy (Diagnostic assessment, Matriculation, and Mini Research). This action research was conducted in the research methodology course in the odd semester 2022-2023 at the Master of Islamic Religious Studies of the Islamic University of Indonesia. The data collection technique used tests, open-ended questions, and questionnaires. The data analysis technique was carried out using quantitative analysis. The research results show that through the application of the DaM2R strategy, there is an increase in students' cognitive abilities as demonstrated by the results of the diagnostic assessment gain (pretest), with the majority of the posttest being in the high category (<g> 0.70). After matriculation, students' knowledge increases from four to 11 abilities. Examining the results of the mini research work that has been prepared, the average score is 90, and the draft thesis proposal presented has an average score of 91. The relevance between the results of the mini research and the draft thesis proposal that was prepared is 87.5% relevant, and 12.5% ​​have changed research ideas and types of research due to student uncertainty and students' lack of confidence in their interest and mastery of the research methodology used.